2017
DOI: 10.3389/fnagi.2017.00240
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Virtual Reality-Based Training Protocol for the Enhancement of the “Mental Frame Syncing” in Individuals with Alzheimer's Disease: A Development-of-Concept Trial

Abstract: A growing body of evidence suggests that people with Alzheimer's Disease (AD) show compromised spatial abilities. In addition, there exists from the earliest stages of AD a specific impairment in “mental frame syncing,” which is the ability to synchronize an allocentric viewpoint-independent representation (including object-to-object information) with an egocentric one by computing the bearing of each relevant “object” in the environment in relation to the stored heading in space (i.e., information about our v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 67 publications
1
89
0
1
Order By: Relevance
“…The major features of VR are aimed at providing easy and intuitive interaction and multidimensional sensory feedback, offering the patient an opportunity to practice activities of daily living that cannot occur in conventional rehabilitation programs, through motivational activities facilitating treatment compliance and customizable on the patient’s characteristics (Rizzo and Kim, 2005 ; García-Betances et al, 2015b ). Therefore, research on VR applied to neurorehabilitation has recently flourished, with increasing evidence of efficacy (Rizzo and Kim, 2005 ; Serino et al, 2017 ; Anderson-Hanley et al, 2018 ; Tieri et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The major features of VR are aimed at providing easy and intuitive interaction and multidimensional sensory feedback, offering the patient an opportunity to practice activities of daily living that cannot occur in conventional rehabilitation programs, through motivational activities facilitating treatment compliance and customizable on the patient’s characteristics (Rizzo and Kim, 2005 ; García-Betances et al, 2015b ). Therefore, research on VR applied to neurorehabilitation has recently flourished, with increasing evidence of efficacy (Rizzo and Kim, 2005 ; Serino et al, 2017 ; Anderson-Hanley et al, 2018 ; Tieri et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The efforts in understanding the relationship between cognitive weaknesses in AD population may also open interesting rehabilitation possibilities. For example, Serino and colleagues found that a VR-based training specifically built for the empowerment of the “Mental Frame Syncing” in a sample of patients with AD led also to an improvement in some tests tapping executive functioning (i.e., Verbal Fluency Test, Verbal Categorical Test, and FAB) [ 37 ]. Influencing higher-order cognitive abilities, such as the executive functions, the spatial reference frames appear to dramatically impact the way individuals categorize information.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the opportunity for an ecological, controlled and secure testing, within virtual environments, it is possible to set-up a “reorientation task” by systematically varying the starting point of the retrieval phase with respect to the encoding phase [ 35 , 36 ]. This strategy (i.e., the virtual disorientation) forces participants to refer to their stored allocentric map and synchronize it with new egocentric input (i.e., the MFS ability) to orient in the environment [ 37 , 38 , 39 ]. In a recent study from our group, we exploited the potential of VR to study the presence of allocentric and syncing deficits in a sample of patients with AD and amnestic MCI.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, has supported its deployment for both clinical and non-clinical samples of elderly people and young adults ( García-Betances et al, 2015 ; De Tommaso et al, 2016 ; Plancher and Piolino, 2017 ). Within medical and neuropsychological settings, VR has been extensively applied as an assessment and a rehabilitation tool for elderly people suffering from consequences of a traumatic brain injury ( Aida et al, 2018 ; Alashram et al, 2019 ; Maggio et al, 2019 ), for post-stroke patients ( Henderson et al, 2007 ; Saposnik and Levin, 2011 ; Laver et al, 2017 ), and for spatial memory and balance ( Allain et al, 2014 ; Serino et al, 2017 ; Gerber et al, 2018 ; Soares et al, 2018 ), among other applications (see Plancher and Piolino, 2017 ; Moreno et al, 2019 ). Crucially, VR allows the therapy to be tailored in a controlled way, according to each disease starting from a continuous assessment of the individual’s behaviors.…”
Section: A New Integrated Approach To MCI Assessmentmentioning
confidence: 99%